Development of Curcumin Encapsulated Liposomes in Chlorhexidine-Loaded Organogel Using Ternary Phase Systems for Treatment of Omphalitis in Infants - Ibilola Mary Cardoso-Daodu; Margaret Okonawan Ilomuanya (Advances in Pharmacological and Pharmaceutical Sciences)
Infections in infants, after childbirth, remain a leading cause of neonatal morbidity and mortality, globally. A soaring percentage of these infections arise from bacterial colonization of the umbilicus. Current therapy for omphalitis includes the topical application of chlorhexidine on the umbilicus. Bacteria such as Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus, which are the key causative organisms of omphalitis, are resistant to chlorhexidine. In this study, curcumin-loaded liposomes were prepared using the “thin film hydration” method. Liposomes were characterized by particle size analysis, light microscopy, encapsulation efficiency, and flux. Stable organogels were formed via a high-speed homogenization method and stabilized by an emulsifier mix. They were evaluated for stability over a period by observing for phase separation. Four gels F1 (curcumin-loaded liposomes in chlorhexidine organogel), F2 (curcumin-loaded liposomes in organogel), F3 (chlorhexidine in organogel), and control (plain organogel) were prepared. Physicochemical properties of all gels were evaluated such as organoleptic tests, gel-to-sol transition, rheological studies, pH, skin irritancy, spreadability, accelerated stability, and antibacterial activity studies. Liposomes were spherical with an average size of 7 μm and an encapsulation efficiency of 97%. The in vitro release profile best fits the Higuchi mathematical model implying that curcumin release was by diffusion and dissolution mechanism. In vitro release was also higher at pH 5.5. F1 had the highest spreadability of 63 mm2g−1 and the lowest viscosity of 184,400 MPas at a shear rate of 10 rotations per minute with a pH of 6.5. Formulation F1 also displayed the highest antibacterial activity against all three bacteria. It can be concluded that the synergistic interaction between curcumin and chlorhexidine may be responsible for the significant antibacterial potency exhibited in formulation F1. Curcumin-loaded liposomes in chlorhexidine organogel (F1) can serve as a prototype for the development of an antibacterial topical formulation having intrinsic activity and enhanced potency to combat omphalitis.